2020
DOI: 10.1371/journal.pone.0241473
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to engagement with contact tracing during infectious disease outbreaks: A rapid review of the evidence

Abstract: Background Until a vaccine is developed, a test, trace and isolate strategy is the most effective method of controlling the COVID-19 outbreak. Contact tracing and case isolation are common methods for controlling infectious disease outbreaks. However, the effectiveness of any contact tracing system rests on public engagement. Numerous factors may influence an individual’s willingness to engage with a contact tracing system. Understanding these factors has become urgent during the COVID-19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 28 publications
9
64
0
Order By: Relevance
“…It requires large numbers of skilled personnel to conduct parallel processes of both contact identification reported by detected cases and reaching out to reported contacts [ 7 , 15 ]. Moreover, contact tracing needs an integrated information and communication system, streamlined processes so the tracing can be done within 72 hours, trustworthy local health institutions to which the population feels they can provide information on contacts, and buy-in from decision-makers and health institutions [ 16 – 19 , 26 , 30 ]. Third, contact tracing efficacy depends on the impact on isolation for those suspected and confirmed cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires large numbers of skilled personnel to conduct parallel processes of both contact identification reported by detected cases and reaching out to reported contacts [ 7 , 15 ]. Moreover, contact tracing needs an integrated information and communication system, streamlined processes so the tracing can be done within 72 hours, trustworthy local health institutions to which the population feels they can provide information on contacts, and buy-in from decision-makers and health institutions [ 16 – 19 , 26 , 30 ]. Third, contact tracing efficacy depends on the impact on isolation for those suspected and confirmed cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, contact tracing faces many challenges in LMICs throughout the policy cycle. Starting at the agenda-setting phase, where decision-makers might struggle to see the immediate value of this strategy compared to its logistical challenges, all the way to the implementation, monitoring, and evaluation where performance might be hard to measure [ 7 , 15 19 ]. Furthermore, implementing a coordinated response across levels of government (national, subnational, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Our Delphi participants also emphasized the importance of enhancing testing and contact tracing . A test, trace and isolate strategy remains the most effective method of controlling the COVID-19 outbreak, until an effective vaccine has been developed [21]. The participants accordingly suggested that government should prioritize efforts to ensure that everyone can get a free, reliable COVID-19 test quickly and receive the results promptly.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of contact tracing and the extent of resources required to implement it successfully will ultimately depend on the social interactions within a population [28]. A recent review suggest that COVID-19 contact tracing systems could be facilitated by: clear communication about contact tracing; involvement of stakeholders in the development of contact tracing systems, particularly, digital applications; evaluation and quality assurance of the contact tracing system [21].…”
Section: Discussionmentioning
confidence: 99%
“…Models by the present authors 7 and others 8 have found that incorporating backwards tracing to identify infector individuals could dramatically increase the efficacy of tracing programs. However, testing delays, mistrust, and low compliance in some communities have undermined the confidence of health authorities in the benefits of TTI 9,10 . Moreover, efficacy sharply decreases when caseloads are high 11 , as is true for SARS-CoV-2 – but not yet B.1.1.7 12,13 – in many regions.…”
mentioning
confidence: 99%